(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The purpose of this study was to determine the totality of teaching using digital literacy during the covid-19 pandemic. The method used is a qualitative method. This study focuses on teachers and students who carry out online learning processes during the covid-19 pandemic, to be precise at SMAN 6 SOPPENG. The sample consists of five English teachers and five students from class XI.MIA.Two. The results showed that the totality of teachers in teaching using electronic devices could be said to be quite good and creative. The teacher’s way of increasing student learning motivation is also innovating, the teacher always encourages, gives direction, and reminds students to continue to be enthusiastic in learning even in situations like today. Teachers try to make teaching methods that they feel are appropriate to be applied and can make it easier for students to understand the material presented in online learning. The teachers also operated and used teaching media (WhatsApp, Zoom Application, Google Classroom) quite well.